Система обліково-аналітичного забезпечення інноваційних підприємств - Одрехівський, М. В.; Наконечний, Б. В.; Odrekhivskyi, M. V.; Nakonechnyj, B. V. (Видавництво Львівської політехніки, 2017)
Проаналізовано організацію системи обліково-аналітичного забезпечення інно- ваційних підприємств (ІП), яка має бути адекватною до ринкових умов господарювання, гнучкою та адаптогенною до умов зовнішнього середовища, сприяти зростанню інвестиційної привабливості ІП, прийняттю оптимальних управлінських рішень та відпрацюванню стратегічних завдань, з метою забезпечення ІП стійкого розвитку.

The paper aims at researching the approaches towards the implementation of the tasks of the system of accounting and analytical provision of Innovational Enterprises (IE). Audit and Analysis of Innovational Enterprises (IE) is predetermined by the demands of functioning and management of their economic mechanism. The subject matter lies in the methodological approaches to the organization of the system of accounting and analytical provision of IE which can be implemented in accordance with the algorithm that includes the following: determination of the standards of research, production and service operations; determination of the working time necessary for the fulfillment of research, production and service operations by the employees; determination of the wage of the working time unit of employees, taking into account the general level of their income; determination of the expenditures on equipment, hardware, tools made of natural resources, other expenses; determination of the percentage share of the salaries among all expenses on innovational activities; determination of the price of innovational goods and services; determination of the cost of innovational goods and services. The object of the present study comprises the process of accumulation, processing and presentation of data about economic activities of IE, systematization, grouping and compiling data in order to receive result-oriented information about economic activities, sufficient provision of the evaluation, analysis and prediction processes with the required data which is targeted at optimal regulation of processes of economic tasks’ fulfillment, control over economic activities. Based on the results presented in the research, it is possible to conclude that the organization of the system of accounting and analytical provision of IE has to be adequate to the market conditions of economic activity, flexible and adaptable to the external conditions as well as to boost the innovational appeal of IE, optimal decision-making and strategic planning that is aimed to provide IE the sustainable development.
The system of accounting and analytical provision of innovational companies
Keywords: аналіз; забезпечення; завдання; інноваційне підприємство; облік; організація; підходи; рішення; система; analysis; provision; task; innovational company; accounting; organization; approaches; decisions; system; 657.62; 658.29